Online Densitometry of Color Proof Patches - ATODA, Oichi; KOBAYASHI, Shinji (Bulletin of the Technical Association of Graphic Arts of Japan, 1986)
An instrumentation for online measurement of patch density in color proof printing is presented. A non-contact density-to-voltage transducer is newly designed, in which both illuminating light and reflected light are sharply focused by two lens systems in order to suppress stray light. Three transducers are conveyed by the carriage of printing machine and scan the printed paper across three corresponding patches. During the scan they sample ink density and send the data to an industry computer, whose program extracts patch data out of stored data sequences based on the feature of data pattern, and computes patch density by averaging and adjusting zero levels to the data on white area preceding patches. It is found through online experiment that our instrumentation is practically applicable, but random float of printed paper causes some fluctuation in resultant density readings. A technique to compensate this error is presented.